SULFORDIOXIDE SOURCES OF EMISSION AND ITS CONCENTRATION AT TWO STATIONS OF TEHRAN - N. Razeghi; K. Imandel; Gh. Jamshidinia; M. Hakimipour; M.H. Monshi (Tehran University of Medical Sciences, 1974)
For determination of SO2 concentration and its variation due to time and location within Tehran air-shed area, department of Environmental Health, School of Public Health installed two units of semiautomatic air sampler, in Tehran University campus and Ghazvin-square area. Collected samples were analyzed according to Hydrogen Peroxide Method and for each month arithmetic mean was calculated. This survey should that this yearly arithmetic average concentration of S02 during sampling period in the above mentioned stations was 106 and 322 percent of allowable concentration of 1971 United States Standard. Calculations based on.1972 formal reports of fossil fuel consumption showed that daily emission of SO2 into Tehran air-shed was 200 tons from which 87.4 and 4.71 percent was due to heavy industries., and transportation vehicles respectively. Collected data showed that the amount of dust fall in Ghazvin-square area was always more than Tehran University campus, but mostly lower than most of the big cities in the world.